The Role and Importance of the Work Called as Mufid (Nazmu't-Teshil) Written by Muhyiddin Mehi in Turkish Language and Medical History - Gozlu, Emel Kaya (Selcuk Univ, Inst Turkish Studies, 2009)
In this study, the work called Mufid (Nazmu't-Teshil), an important medical book having been written with Old Anatolia Turkish by Muhyiddin Mehion Hegira 871 / Christian era 1467 and copied by Serefeddin Sabuncuoglu on Hegira 872/ Christian era 1468 is tried to make a detailed definition and is tried to put forth its importance in terms of Turkish language and medical history of fifteenth century.
Keywords: Muhyiddin Mehi; Mufid; Sabuncuoglu; history of medicine; terms of medicine